Returning home: reintegration after prison or jail - Bahr, Stephen J. (NASW Press, 2015)
Introduction -- Preparation for reintegration -- The reintegration process -- Living arrangements : the impact of where and with whom you live -- Training and employm ent : preparing for self support -- Family relationships : how family bonds can support or interfere with success -- Friends and frenemies : how peers can help or hinder success -- Overcoming substance abuse and dependency : a key to success -- Mental health challenges : stacking the odds against success -- Social context : neighborhood and community influences -- Programs and policies -- A look back and a look forward